THE ROLE OF ADVERBIAL CLAUSES AND CLEFT SENTENCES IN COMPLEX SENTENCE FORMATION (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides a detailed exploration of complex sentences with adverbial clauses and cleft sentences, focusing on their structure, purpose, and practical applications. It begins by defining complex sentences and categorizing adverbial clauses into five types: time, place, reason, purpose, and condition. Examples are included to illustrate their use in various contexts. The article then transitions to cleft sentences, explaining their role in emphasizing specific elements of a sentence. Key types of cleft constructions, such as it-cleftsand what-clefts, are discussed with examples. The piece concludes with practical